(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
This communication portrays the molecular characterization and confirms the new reports of two fresh water green algae namely, Pithophora polymorpha Wittrock and Spirogyra maxima (Hassall) Wittrock from Bangladesh. The samples of these algal species were cultured and partial 18S rDNA was sequenced and analysed for their molecular identification. It was found that the primers reported here could sufficiently identify these algae as P. polymorpha and S. maxima. Furthermore, the Neighbour joining (NJ) tree generated from 18s rDNA sequences suggested that Spirogyra maxima of Bangladesh is distantly related to the cluster of S. juergensii and S. platensis. Pithophora polymorpha along with P. roettleri, P. sano and Pithophora sp. seems to form a strongly supported monophyletic group. The alga AP1 clusters with Pithophora and the alga AS1 clusters with Spirogyra. This study is the first-time report of molecular identification of Bangladeshi algae and a landmark towards the future exploration of the algal biodiversity of Bangladesh.